Money Laundering Criminal Liability Through Crypto Asset Exchange in Indonesia - I Nyoman Sucitrawan; , M Arief Amrullah; Tanuwijaya, Fanny Tanuwijaya (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
Cryptocurrency users, including those utilizing Bitcoin, Litecoin, Dogecoin, and others, are increasingly prevalent in Indonesia. Since the Rupiah is the only legal currency in Indonesia, cryptocurrencies cannot be used as a means of payment or exchange in financial transactions within the country. However, cryptocurrencies are considered investments when incorporated into commodities, becoming crypto assets that can be used as digital investment assets. This research employs normative legal research to explore legal principles and norms to address legal questions. If someone exchanges assets obtained from criminal activities for crypto assets, thinking they are legitimate, and if the money in these crypto assets is derived from criminal proceeds, such actions constitute money laundering (ML). This process involves purchasing crypto assets with illicit gains, exchanging Rupiah for cryptocurrency, or converting Rupiah into cryptocurrency. While cryptocurrency is recognized as a legal digital commodity for investment purposes in Indonesia, it becomes illegal when misused by individuals seeking to legitimize wealth obtained illegally. Converting illegally acquired wealth into cryptocurrency to deceive the government and make the transaction appear lawful may result in legal consequences